2020
DOI: 10.36469/jheor.2020.17088
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Next Generation Sequencing Panel using Circulating Tumor DNA in Patients with Advanced Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: Background/Objectives: Until now, no meta-analysis has been published to evaluate the diagnostic performance of next-generation sequencing (NGS) panel using circulating tumor (ctDNA) in patients with advanced non-small cell lung cancer (aNSCLC). The aim of the study was to carry out a systematic review and a meta-analysis in order to determine the accuracy of NGS of ctDNA to detect six oncogenic driver alterations: epidermal growth factor receptor (EGFR); anaplastic lymphoma kinase (ALK); ROS proto-oncogene 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Previous meta-analyses mostly reported ctDNA performance at the patient level 18,22,23 or did not specify the data level. 19,20 We used sample-level data to facilitate diagnostic performance by driver mutation as well as mutation class, which allows for a more detailed assessment of the CV of ctDNA testing and more mutation-specific information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous meta-analyses mostly reported ctDNA performance at the patient level 18,22,23 or did not specify the data level. 19,20 We used sample-level data to facilitate diagnostic performance by driver mutation as well as mutation class, which allows for a more detailed assessment of the CV of ctDNA testing and more mutation-specific information.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies published between January 2012 and July 2023 were identified by searching MEDLINE and Embase databases with predefined search strategies (Supplementary File, Table S2) through the Embase platform. Furthermore, the official websites of three commonly used ctDNA tests (Guardant360 ® CDx, InvisionFirst ® -Lung, and FoundationOne ® Liquid CDx) as well as reference lists of included studies and previous systematic literature reviews [18][19][20][21][22][23][24][25][26] were searched for additional potentially eligible studies.…”
Section: Study Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-small cell lung cancer (NSCLC) accounts for approximately 87% of all lung cancer patients [ 2 ]. Among these, 40% are adenocarcinoma, 25–30% are squamous carcinoma and 10–15% are large cell carcinomas [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the era of precision medicine, NSCLC has become an eminent example of how therapeutic decision making is based on the identification of specific biomarkers, called oncogenic drivers, designed by the National Comprehensive Cancer Network (NCCN) guidelines, such as the epidermal growth factor (EGFR), rearrangements of anaplastic lymphoma kinase (ALK), ROS proto-oncogene1 (ROS1), serine/threonine-protein kinase B-Raf (BRAF), ERBB2, MET proto-oncogene, receptor tyrosine kinase (MET) exon 14 skipping, RET proto-oncogene (RET) and PDL-1 (programmed death ligand 1) [ 4 , 5 ] present in approximately 30% of NSCLC patients [ 3 , 6 , 7 ]. More recently, the G12C missense mutation of the Kirsten rat sarcoma viral oncogene homolog (KRAS) gene has been added to these and new therapeutic agents (i.e., adagrasib, sotorasib) have been developed [ 8 ].…”
Section: Introductionmentioning
confidence: 99%